The 65th anniversary of Professor Ihor Stasyuk (Condensed Matter Physics, 2003)
On 23 September 2003, Professor Ihor Stasyuk, Research Deputy Director and
Head of the Quantum Statistics Department of the Institute for Condensed Matter
Physics will celebrate his 65th birthday.
Professor Ihor Stasyuk is a prominent Ukrainian scientist and high school teacher,
Corresponding Member of the National Academy of Sciences of Ukraine, Doctor of
Science in Physics and Mathematics.